Liposomal Nanoformulation-encapsulated Paclitaxel for Reducing Chemotherapy Side Effects in Lung Cancer Treatments: Recent Advances and Future Outlooks - Mohammad-Jafari, Kave; Naghib, Seyed Morteza; Mozafari, M.R. (Current Medicinal Chemistry, 2025)
Paclitaxel is one notable chemotherapy drug that is used to treat a number of cancers, including lung cancer. Nevertheless, it has drawbacks such as toxicity, low solubility in water, and the emergence of multidrug resistance (MDR). This article reviews the use of liposomal formulations to improve paclitaxel administration and efficacy for lung cancer therapy. Paclitaxel's pharmacological characteristics can be improved by liposomes through increased solubility, extended circulation, passive tumor targeting through leaky vasculature, and decreased side effects. Recent developments in paclitaxel liposomal formulations, including as cationic liposomes, conventional liposomes, targeted liposomes with particular ligands, and liposome-loaded microorganisms, are outlined in this article. In comparison to free paclitaxel, these nanoformulations exhibit enhanced cytotoxicity, cellular uptake, apoptosis, tumor growth suppression, and anticancer effects in lung cancer cell lines and animal models. One efficient way to get around the drawbacks of paclitaxel is to alter its size, makeup, and surface characteristics. This will let the medication accumulate and penetrate tumors more easily, avoid multidrug resistance, and cause less systemic toxicity. The article explores clinical studies showcasing the safety and therapeutic efficacy of liposomal paclitaxel for individuals afflicted with lung cancer. In its entirety, the document provides an in-depth examination of the potential enhancement in paclitaxel's dispersion and anti-tumor impacts through the utilization of liposomal technology when addressing diverse manifestations of lung cancer.
Keywords: liposomal nanoformulation